2008
DOI: 10.5897/ajb2008.000-5044
|View full text |Cite
|
Sign up to set email alerts
|

Ecological effects of some heavy metals (Cd, Pb, Hg, Cr) pollution of phytoplanktonic algae and zooplanktonic organisms in Sarıyar Dam Reservoir in Turkey

Abstract: Accumulation of heavy metals (Cd, Pb, Hg, Cr) in water and plankton of Sarıyar Dam Lake (SDR) was seasonally studied from April, 2000 to December, 2004. In addition, seasonal changes in phytoplankton and zooplankton populations and species abundance were also determinate. Some physio-chemical parameters of water and their correlation with heavy metals were also determinated. The dominant phytoplanktonic algae determined were Choroococcus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(6 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…This is because As, especially (AsO 4 ) 3− , competes with inorganic P transporters. Atici et al [28] observed the seasonal variation in the patterns of heavy metal accumulation and the stress of the phytoplankton in a freshwater body, Sariyar Dam Lake in Turkey. The heavy metal accumulation pattern in plankton samples in all four seasons was the same as Pb > Cr > Cd > Hg, in agreement with the bioavailability of these metals in the same order in the lake water samples of the freshwater system, showing a directly proportional relationship between metal abundance and bioabsorption by phytoplankton.…”
Section: Behaviour Of Heavy Metals In An Aquatic Ecosystemmentioning
confidence: 99%
“…This is because As, especially (AsO 4 ) 3− , competes with inorganic P transporters. Atici et al [28] observed the seasonal variation in the patterns of heavy metal accumulation and the stress of the phytoplankton in a freshwater body, Sariyar Dam Lake in Turkey. The heavy metal accumulation pattern in plankton samples in all four seasons was the same as Pb > Cr > Cd > Hg, in agreement with the bioavailability of these metals in the same order in the lake water samples of the freshwater system, showing a directly proportional relationship between metal abundance and bioabsorption by phytoplankton.…”
Section: Behaviour Of Heavy Metals In An Aquatic Ecosystemmentioning
confidence: 99%
“…7389 Tahun 2009 tentang Batas Maksimum Cemaran Logam Dalam Pangan dengan Nilai Logam Berat Kadmium (Cd) adalah 100 ppb atau 0,1 mg/L. Logam berat di lingkungan perairan merupakan jenis pencemaran utama yang mengancam kehidupan perairan dan manusia serta memiliki efek negatif yang dapat mengganggu keseimbangan ekologi lingkungan dan keanekaragaman organisme perairan (Atici, 2008). Kontaminan logam berat yang masuk ke dalam tubuh ikan nila (Oreochromis niloticus) melalui beberapa cara, yaitu sistem sirkulasi (peredaran darah) dan sistem ekskresi.…”
Section: B Pembahasanunclassified
“…Fish from freshwater are majorly exposed to various heavy metals, which are added into the water bodies through the different-different sources. Contamination of these heavy metals into aquaculture has intensified global issues because it shows a risk to fish and has harmful impacts on fish buyers [71]. There are three different modes through which heavy metals enter the fish.…”
Section: Effect On Aquatic Environmentmentioning
confidence: 99%